Characterization of a Chinese lignite and the corresponding derivatives using direct analysis in real time quadrupole time-of-flight mass spectrometry. Issue 107 (7th November 2016) - Fan, Xing; Wang, Chu-Fan; You, Chun-Yan; Wei, Xian-Yong; Chen, Lu; Cao, Jing-Pei; Zhao, Yun-Peng; Zhao, Wei; Wang, Yu-Gao; Lu, Jin-Li
Abstract : Direct analysis in real time ionization technique coupled with a quadrupole time-of-flight mass spectrometry (Q-TOF MS) was applied to characterize raw coal and coal derivatives in the solid state. Abstract : Direct analysis in real time (DART) ionization technique coupled with a quadrupole time-of-flight mass spectrometry (Q-TOF MS) with high resolving power was applied to characterize raw coal and coal derivatives in the solid state. Desorption and ionization under optimized parameters allowed for the detection of small molecules scattered inside pores of a macromolecular network of raw coal. Use of the second-stage MS (Q-TOF) significantly contributed to the structural elucidation of compounds in coal and coal derivatives.